Объяснение:
(3-5,8x)-(2,2x+3)=16
3-5,8x-2,2x-3=16
-8x=16
x=-16/8=-2
6x-5(3x+2)=5(x-1)-8
6x-15x-10=5x-5-8
-9x-10=5x-13
5x+9x=13-10
14x=3
x=3/14
(3x+7)/2=(6x+4)/5
5(3x+7)=2(6x+4)
15x+35=12x+8
12x-15x=35-8
-3x=27
x=-27/3=-9
x/4 -(x-3)/5=-1
(5x-4(x-3))/(4*5)=-1
5x-4x+12=-20
x=-20-12=-32
(8x-3)/7 -(3x+1)/10=2
(10(8x-3)-7(3x+1))/(7*10)=2
80x-30-21x-7=70*2
59x-37=140
59x=140+37
x=177/59=3
(15x+27)(-5x-9)=0
15x+27=0
15x=-27
x1=-27/15=-9/5=-1 4/5=-1,8
-5x-9=0
5x+9=0
5x=-9
x2=-9/5=-1,8
ответ: x=-1,8.
|8x-4|-7=13
8x-4=13+7
8x-4=20
8x=20+4
x1=24/8=3
8x-4=-20
8x=-20+4
x2=-16/8=-2
1.(cos(3*пи/2 - a) + cos(пи+a)) / (2*sin(a-пи/2) * cos(-a) +1)
(sin(a)+cos(a))/(2*cos(a)^2-1)
-1/(sin(a)-cos(a))
2.x ∈(пи*k/2-пи/8), k ∈ Z
3.a∈(-∞, пи*k)⋃(пи*k, пи*k+пи/2)⋃(пи*k+пи/2, ∞)